Dinamika Regulasi Hukum Investasi dan Dampaknya terhadap Kepastian Bisnis - Nike Cahyaningrum; Mira Eka Erlina; Rahma Rini Khalisa Firdausi; Chammellia Annastasya Melati4; Rahma Syifa Az Zahra; Irma Salvia Nisrina; Diana Setiawati (Pusat Riset dan Inovasi Nasional, 2025)
Investment plays a strategic role in driving economic growth and job creation. However, the dynamics of investment law regulation in Indonesia still face various challenges that impact business certainty for investors. This study aims to: (1) analyze the dynamics of investment law regulations in Indonesia over time until the enactment of the Job Creation Law; (2) identify the forms of investment law regulations and the challenges of their implementation; and (3) formulate legal solutions to improve business certainty for investors. The research method used is normative legal research with a legislative and conceptual approach. Data was obtained from relevant regulations, scientific journals, and academic literature, then analyzed using descriptive-qualitative methods. The results of the study show that although regulations such as Law No. 25 of 2007 and the Job Creation Law have strengthened the legal framework for investment, their implementation is still hampered by bureaucracy, inconsistencies between central and regional policies, and weak oversight in digital investment. The conclusion of this study is that regulatory harmonization, strengthening arbitration institutions, and improving legal literacy are important steps to enhance legal certainty and investment attractiveness in Indonesia.